(untitled) (Bangladesh Journal of Zoology, 2015)
Avifauna of village Pashukhali and Gajdhar in the district of Netrokona, Bangladesh was carried out during July 2003-June 2004. A total of 101 species of birds belonging to 12 orders, 35 families and 82 genera were recorded. Out of 101 species, 61 (60.4%) were non-passerine and 40 (39.6%) were passerine. Among them, 80 (79.2%) were resident and 21 (20.8%) were migratory birds. Of the non-passerine birds, 15 (24.6%) were migratory and 46 were (75.4%) resident. While in passerine birds, 6 (15%) were migratory and 34 (85%) were resident. Of the total species, 18 (17.8%) were locally found to be very common, 41 (40.6%) were common, 29 (28.7%) fairly common and 13 (12.9%) rare or few. Out of 101 species, highest numbers (58.4%) of species were widely distributed. Maximum numbers of birds (78.2%) were terrestrial. Bangladesh J. Zool. 42(2): 141-152, 2014